La ética en el ejercicio del nutricionista-dietista (2004)
ABSTRACT: In this communication ethics is conceived as a philosophical discipline enabling us to reflect, argue and to elaborate proposals for a professional practice able to preserve human dignity and human rights regarding nutrition, nourishment and health. Aranguren´s dictum: "; Moral contents originate in our idea of the human being"; lead us to question ourselves about how is the concept of the nutricionist-dietician about the human being that is cared for in the aspects related to nourishment and nutrition.